Current Australian speech-language pathology practice in addressing psychological well-being in people with aphasia after stroke. - Sekhon, Jasvinder K.; Douglas, Jacinta; Rose, Miranda L. (International Journal of Speech-Language Pathology, 2015)
Purpose: Psychological well-being is essential to overall health; however, there is a paucity of research on how to address psychological well-being in stroke survivors with aphasia. This study describes the current beliefs, attitudes and practices of Australian speech-language pathologists in addressing psychological well-being in people with aphasia after stroke. Method: A 26-item web-based survey consisting of open and closed questions was distributed to Australian speech-language pathologists through four electronic databases. Result: Australian speech-language pathologists ( n = 111) utilized counselling and clinical approaches to address psychological well-being in people with post-stroke aphasia. The majority of speech-language pathologists did not feel comfortable with addressing psychological well-being in people with aphasia and sought support from other health professionals in this practice. Self-perception of being under-skilled was the main barrier identified to adequate practice in this domain, followed by inadequate time, inadequate staffing and people with aphasia declining referral to counselling. The main facilitators reported by speech-language pathologists to address psychological well-being included personal interest, personal and professional experience and availability of counselling health professionals for people with aphasia. There were small-to-medium statistically significant correlations between speech-language pathologists reporting additional training in counselling and perceived knowledge of, confidence in and satisfaction with managing psychological well-being in people with aphasia. Conclusion: This study identifies factors requiring attention in order to enable speech-language pathologists to facilitate improved psychological well-being in people with aphasia.